S135 A retrospective multi-centre study of the effects of allogeneic haematopoietic stem cell transplantation on pulmonary function. (2nd December 2011) - Dharmagunawardena, R T; Pearce, R M; Lee, J; Apperley, J F; Littlewood, T; Wilson, K M; Orchard, K; Jackson, G; Snowden, J A; Kirkland, K; Cook, G; Hubbard, R; et al.
Abstract : Introduction: Allogeneic haematopoietic stem cell transplantation (HSCT) is often complicated by serious pulmonary complications including severe infections, drug toxicity and graft vs host disease. However, there is limited data on the prevalence of significant lung function defects in long-term survivors. Method: We undertook a UK wide, multi-centre, retrospective study of the effects on pulmonary function in adult patients undergoing HSCT over a 4-year period. Pulmonary function tests (PFT) were evaluated at baseline (pre-transplant) and 12 months post-transplant. Impaired pulmonary function was defined as FEV1 or FVC less than 80% predicted. Results: 532 allogeneic HSCTs were registered in the BSBMT database, having been performed at 6 centres over the 4-year study period. 157 patients underwent PFT pre-HSCT and at least 6 months post-BMT, with 12-month data available for 90 patients (Abstract S135 table 1 ). The median age was 42 years (range 18–69) and 59% of patients were male. Median FEV1 and FVC were 98.9% and 101% predicted respectively for patients pre-HSCT, with 25 (15.9%) patients having impaired lung function pre-HSCT. For patients with normal PFT pre-HSCT, 13 (10%) had impaired PFT at 12 months with median reduction in FEV1 of 1.33 L (33.5%) (range 0.59–2.25) and FVC of 1.29 L (28.9%) (range 0.17–3.33). 38% had obstructive, 46% restrictive and 15% mixed picture spirometry pattern. 69% of patients with newly impaired PFT had acute graft vs host disease, (p=0.068). No statistically significant predictive factors were identified for newly impaired PFT: age, sex, total body irradiation, Alemtuzumab treatment, transplant intensity and type of donor. For patients with impaired PFT at baseline, 11 (44%) remained impaired at 12 months with no significant fall in spirometry values (median FEV1 fell 2% and FVC rose 2%). Conclusion: Although these data represent only a proportion of patients undergoing allogeneic HSCT, we found 10% of patients developed impaired PFT at 12 months with large falls in FEV1 and FVC. These data suggest there may be as many as 60 to 120 HSCT recipients each year developing major impairment of lung function. Multi-centre prospective studies are required to fully characterise the frequency and risk factors for impaired PFT post-HSCT.